2013
DOI: 10.1107/s1744309113031114
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, crystallization and preliminary X-ray diffraction analysis of the aspartate transcarbamoylase domain of human CAD

Abstract: Aspartate transcarbamoylase (ATCase) catalyzes the synthesis of N-carbamoyl-L-aspartate from carbamoyl phosphate and aspartate in the second step of the de novo biosynthesis of pyrimidines. In prokaryotes, the first three activities of the pathway, namely carbamoyl phosphate synthetase (CPSase), ATCase and dihydroorotase (DHOase), are encoded as distinct proteins that function independently or in noncovalent association. In animals, CPSase, ATCase and DHOase are part of a 243 kDa multifunctional polypeptide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…huATCase Exhibits Positive Cooperativity for Substrate Binding huATCase was purified as previously reported (Ruiz-Ramos et al, 2013). Based on thermal shift assays, huATCase was stable at pH 6-9, with a melting temperature (T M ) of 54 C ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…huATCase Exhibits Positive Cooperativity for Substrate Binding huATCase was purified as previously reported (Ruiz-Ramos et al, 2013). Based on thermal shift assays, huATCase was stable at pH 6-9, with a melting temperature (T M ) of 54 C ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Purification was as reported by Ruiz-Ramos et al (2013) with one additional step. Prior to the final size-exclusion chromatography step, the sample was loaded onto a HiTrap Heparin column (GE Healthcare) in 20 mM Tris-HCl (pH 7), 75 mM NaCl, 5% glycerol, and 2 mM b-mercaptoethanol, and eluted in a linear NaCl gradient.…”
Section: Experimental Procedures Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide BLAST analysis also shows 37% identity (86% query cover) to the ATC domain of human CAD (carbamoyl phosphate synthetase 2, aspartate transcarbamylase and dihydroorotase) protein. The crystal structure of this domain is not yet available, although preliminary data have been reported (Ruiz-Ramos et al, 2013). Further analysis with the PlasmoAP tool (Foth et al, 2003) showed a strong prediction for the N-terminal region to contain an apicoplast-targeting sequence, with a possible cleavage site between residues 27 and 28 (IRT-KK; Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Santiago Ramón-Maiques (Spanish National Cancer Research Centre, Spain) described the crystal structure and function of the DHOase and ATCase domains of human CAD using site directed mutagenesis in combination with MALS (multi-angle static light scattering) (Ruiz-Ramos et al, 2013;GrandeGarcia et al, 2014). Sergio de Cima and Carmen Díez Fernandez from Vicente Rubio's lab (Instituto de Biomedicina de Valencia) further enlightened us about CPS1 (carbamoyl phosphate synthetase I).…”
mentioning
confidence: 99%